GRAMMATICAL EQUIVALENCE IN THE INDONESIAN TRANSLATION OF TOTTO-CHAN NOVEL: THE LITTLE GIRL AT THE WINDOW - Senadaman Wau; Restu Damai Laia; Sohan Putra Amazihono (Jurnal Education and Development, 2021)
This research aimed at analyzing the grammatical equivalence between English version as source text and Indonesian version as translated text of Totto-chan Novel: The Little Girl at the Window. This research was designed in qualitative research design. The result of this research showed that there were five grammatical categories found. They were number, gender, person, tense and aspect, and voice. Singular or plural forms was translated into either singular or plural form, feminine or masculine form was translated into feminine, masculine or general, and pronouns were translated into pronouns.Tense and aspect, past, present and future were translated by using temporal determiners and adverb of time, meanwhile for voice category, active or passive voice was translated into either active or passive.It was concluded that grammatical equivalence used to get the closest meaning.